1983
DOI: 10.1002/j.1460-2075.1983.tb01427.x
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of expression of chick delta-crystallin genes in lens differentiation and in trans-differentiating cultured tissues.

Abstract: During development of the vertebrate lens, the lens epithelium undergoes a final stage of differentiation into lens fibre cells. Lens fibre cells can also be produced by trans‐differentiation from certain extralenticular structures, all of which are of different developmental origin from lens, including embryonic neural retina and retinal pigmented epithelium. Delta‐crystallin is the major lens protein in the chick and appears first in development; it is the major product in trans‐differentiated retina of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Chick tissues which can transdifferentiate to the lens phenotype express low levels of a-, 0-, and 6-crystallins [15,16,521 and their RNAs [2, 3, 10, 24, 281. All the available evidence suggests that although low levels of a-, pand 6-crystallin RNAs and antigens are present in 8 day embryo retina, these fall below detectable levels after cell dissociation and then reappear and accumulate differentially prior to lentoid body formation ( [ 10,24,521 and Figs. 6,8).…”
Section: Lens Cell Differentiation Transdifferentiation and Crystallmentioning
confidence: 99%
“…Chick tissues which can transdifferentiate to the lens phenotype express low levels of a-, 0-, and 6-crystallins [15,16,521 and their RNAs [2, 3, 10, 24, 281. All the available evidence suggests that although low levels of a-, pand 6-crystallin RNAs and antigens are present in 8 day embryo retina, these fall below detectable levels after cell dissociation and then reappear and accumulate differentially prior to lentoid body formation ( [ 10,24,521 and Figs. 6,8).…”
Section: Lens Cell Differentiation Transdifferentiation and Crystallmentioning
confidence: 99%
“…Around lens placodal stage, lens development involves up‐regulation of L‐Maf expression in chick and c‐Maf expression in mouse (Ogino and Yasuda,1998; Kawauchi et al,1999). Somewhat later, the first step of primary lens fibre differentiation occurs, which involves up‐regulation of crystallin proteins, where δ‐crystallin is the first crystallin protein up‐regulated in chick (Shinohara and Piatigorsky,1976; Bower et al,1983; Reza and Yasuda,2004b). The δ‐crystallin enhancer constitutes three Sox2, two Pax6, and two Maf binding sites (Muta et al,2002).…”
Section: Introductionmentioning
confidence: 99%
“…Crystallin expression is associated with lens fiber differentiation (Wistow and Piatigorsky, 1988), in which δ-crystallin is the first crystallin protein up-regulated in chicks (Shinohara and Piatigorsky, 1976; Bower et al ., 1983). We previously showed that after L-Maf up-regulation at HH13, the onset of δ-crystallin expression is BMP independent (Pandit et al ., 2011), which also is confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…By the lens vesicle stage, posterior lens cells exit from the cell cycle and differentiate into primary lens fiber cells, whereas the anteriorly situated lens epithelial cells retain a high proliferative capacity (Modak et al ., 1968). The first step of primary lens fiber differentiation involves up-regulation of crystallin proteins, where δ-crystallin is the first crystallin protein up-regulated in chicks (Shinohara and Piatigorsky, 1976; Bower et al ., 1983; Reza and Yasuda, 2004). During later stages of development, the proliferation rate of lens cells gradually declines, but it never ceases completely, and secondary fiber cells will be generated throughout life.…”
Section: Introductionmentioning
confidence: 99%